OPTIMIZATION OF BIOMASS CULTURE YIELD AND L-DOPA COMPOUND IN THE CALLUS CULTURE FROM COTYLEDONARY LEAVES OF MUCUNA PRURIENS - JANARTHANAM, B.; SUMATHI, E. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Â The objective of the present study was to evaluate the optimization of callus biomass culture yield and high-performance liquid chromatography (HPLC) analysis of L-DOPA compound in the callus culture from cotyledonary leaves of Mucuna pruriens Methods : M. pruriens seed explants were inoculated onto Murashige and Skoog medium supplemented with different concentrations of 2-isopentenyl adenine (2iP) and Gibberellic acid (GA3)Â for germination of plants. The in vitro cotyledonary leaf and hypocotyl explants were cultured on MS basal media containing various concentrations of 2,4-dichlorophenoxyacetic acid (2,4-D), 1- Naphthaleneacetic acid (NAA), 6-Benzylaminopurine (BA) and 2iP for callus induction. A standard approach of Latin square method was followed for screening of media to establish optimum culturing of callus by manipulating the concentration of auxins (2, 4-D, Indole-3-acetic acid (IAA) and NAA) and cytokinins (BA and 2iP) alone and in combinations. The harvested callus biomass was screened for a major metabolite namely L- Dopa compound using HPLC. Results: Cotyledonary leaf explants showed better callus initiation than hypocotyl explants. Maximum callus induction was observed in Murashige and Skoog (MS) medium containing 4.92ÂµM 2iP. Further screening of callus culture was carried out on MS medium supplemented with different concentrations and combinations of 2, 4-D, NAA, Â IAA, (BA) Â and 2iP individually and in combinations. Optimum callus biomass of 21.63 g/L dry weight (246.31 g/L fresh weight) was developed on MS media containing 2.26ÂµM 2, 4-D, 2.22ÂµM BA and 4.92ÂµM 2iP. The harvested callus biomass was subjected to extraction and purification of L- Dopa compound. Conclusion: The present study concludes that Â HPLC analysis of cell biomass extracts in comparison Â with extracts from seeds of mother plants of Mucuna prurienss showed main component of L- Dopa was present in sufficiently large amounts in the undifferentiated cultured cells. Keywords: Mucuna pruriens, Callus biomass, L-Dopa, HPLC analysis